2014
DOI: 10.1089/end.2013.0125
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Varicocelectomy: A Comparative Study of Conventional Laparoscopic and Laparoendoscopic Single-Site Approaches

Abstract: LESSV is comparable to LV in the pediatric population. Our initial experience indicates that the LESS approach may be more painful in the immediate postoperative period than conventional laparoscopy. The LESS technique warrants further evaluation to determine if one approach is clearly more advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Table 1 depicts the study characteristics and methodology for the six studies included in the systematic review (Bansal et al 2014; Friedersdorff et al 2013; Lee et al 2012; Marte et al 2014; Wang et al 2014; Youssef and Abdalla 2015). Among these, three were randomized controlled trials (level of evidence 2b) (Lee et al 2012; Wang et al 2014; Youssef and Abdalla 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 depicts the study characteristics and methodology for the six studies included in the systematic review (Bansal et al 2014; Friedersdorff et al 2013; Lee et al 2012; Marte et al 2014; Wang et al 2014; Youssef and Abdalla 2015). Among these, three were randomized controlled trials (level of evidence 2b) (Lee et al 2012; Wang et al 2014; Youssef and Abdalla 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, three were randomized controlled trials (level of evidence 2b) (Lee et al 2012; Wang et al 2014; Youssef and Abdalla 2015). Another three were retrospective case control studies (level of evidence 3b–4) (Bansal et al 2014; Friedersdorff et al 2013; Marte et al 2014). All publications reported on similar outcomes (i.e., hospital stay, operating time, pain score, time to return to normal activity, complications).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] A recent randomised controlled trial showed that patients who underwent SIL cholecystectomy experienced less postoperative pain and required fewer analgesics compared to those treated with conventional laparoscopic cholecystectomy. [21] As reported by Bansal et al in their initial experience, the author indicates that the laparoendoscopic single-site varicocelectomy may be more painful in the immediate post-operative period than conventional laparoscopy, [22] whereas, Wang et al [23] in their experience, concludes that compared with conventional laparoscopic technique, laparoendoscopic single-site varicocelectomy may decrease post-operative pain and hide the surgical incision better within the umbilicus. [23] In our experience, the patients presented a significantly lower VAS at 6, 9, and 24 post-operative hours.…”
Section: Discussionmentioning
confidence: 96%
“…Son zamanlarda varikoselektomi, konvansiyonel laparoskopi yerine laparoendoskopik single-site (LESS) yaklaşımla da yapılmaktadır. Bu teknikte ilave portun kullanılmaması avantaj olarak düşünülebilir ancak daha fazla deneyim gerektirir (53) . Konvansiyonel laparoskopi ile LESS'in karşılaştırıldığı bir çalışmada, LESS tekniğinde istatistiksel olarak anlamlı saptanmasa da operasyon süresinin daha kısa sürdüğü, postoperatif ağrının LESS tekniğinde daha fazla olduğu, postoperatif hidrosel gelişimi açısından ise fark olmadığı raporlanmıştır (53) .…”
Section: Varikosel Cerrahisinde Laparoskopinin Yeriunclassified